Synthesis of Planar Reflective Gratings for Silicon Interconnects. (5th May 2008) - Millett, Ronald; Ramsey, Jamie; Bock, Przemek; Nkanta, Julie; Schriemer, Henry; Hall, Trevor J.; Bidnyk, Serge
Abstract : The design and simulations of planar reflective gratings for building optical interconnects in silicon-on-insulator (SOI) were studied for a range of silicon core thicknesses of 0.1 to 10 μ m. The verticality of the grating facets has been shown to be the main contributing factor to the cumulative crosstalk in thick silicon cores. The dispersion property of the slab was found to limit the minimal thickness of the core for polarization-insensitive gratings. The effects of polarization-dependent confinement on optical crosstalk were studied. The findings were used to design and simulate a polarization-insensitive 18-channel coarse wavelength division demultiplexer (CWDM) with a free spectral range of over 600 nm. The CWDM demultiplexer uses a 1.7 μ m silicon core and combines a shallow-etch tapered rib structure and multimode silicon channels to produce box-like passbands for integrated receiver applications. The diffraction grating was constructed using double astigmatic point design with phase-corrected grating facets to reduce astigmatism. Optical properties of the planar gratings have been simulated using quasivectorial diffraction grating theory. The simulation results confirm that there is high diffraction efficiency and low optical crosstalk over the entire range of operation. Applications of planar silicon gratings to the synthesis of silicon interconnects are discussed.